2018
DOI: 10.1021/acs.jpcc.8b11493
|View full text |Cite
|
Sign up to set email alerts
|

Bay-Linked Perylenediimides are Two Molecules in One: Insights from Ultrafast Spectroscopy, Temperature Dependence, and Time-Dependent Density Functional Theory Calculations

Abstract: Bay-linked diperylenediimide (di-PDI) molecules are finding increasing use in organic electronics because of their steric hindrance that “twists” the two monomer units relative to one another, decreasing molecular aggregation. In this paper, we explore the electronic spectroscopy and ultrafast dynamics of the singly linked β-β-S-di-PDI (2,9′-di­(undecan-5-yl)-2′,9-di­(undecan-6-yl)-[5,5′-bianthra­[2,1,9-def:6,5,10-d′e′f′]­diisoquinolin]-1,1′,3,3′,8,8′,10,10′(2H,2′H,9H,9′H)-octaone). Excitation–emission spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 51 publications
(125 reference statements)
1
16
0
Order By: Relevance
“…36 There is also precedence for this type of dual emissive behavior in twisted A-D-A complexes. 37,54 Correspondingly, the uniform emission observed in the fused dimer is likely a consequence of the locked structure imparted by the ring fusion. It is also of note that the fused CT transition has a lifetime of more than a factor of three greater than that of the non-fused CT, despite the two being very similar in energy (2.06 eV vs. 1.95 eV).…”
Section: Characterization Of Charge Transfer Lifetime With Timeresolvmentioning
confidence: 96%
See 2 more Smart Citations
“…36 There is also precedence for this type of dual emissive behavior in twisted A-D-A complexes. 37,54 Correspondingly, the uniform emission observed in the fused dimer is likely a consequence of the locked structure imparted by the ring fusion. It is also of note that the fused CT transition has a lifetime of more than a factor of three greater than that of the non-fused CT, despite the two being very similar in energy (2.06 eV vs. 1.95 eV).…”
Section: Characterization Of Charge Transfer Lifetime With Timeresolvmentioning
confidence: 96%
“…Ring-fused complexes have been shown to exhibit superior efficiency to their non-fused counterparts when tested in OPV devices. [15][16][17][18]34,35 Great strides have been made in improving device efficiency through such synthetic routes, however there have been few studies [36][37][38][39] focused on electronic processes in these increasingly complex molecules. Photoexcitation is the rst in a series of ultrafast processes that lead to exciton generation, charge separation, and charge carrier transport in photovoltaic materials, so understanding the molecular excited state/excitonic properties can be crucial for controlling photophysical processes and informing molecular design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insight into the optical properties, the UV/Vis absorption and emission spectra of PDI 4 e and PDI 4 i were measured and compared to each other and reference compounds PDI 1 and PDI 2 . It has been frequently observed that the absorption profile of PDI is highly sensitive to its environment, especially the presence of folding, [38,39] or aggregates with H-or J-coupling. [40,41] First, looking at the absorption profiles in chloroform (Figure 5A) all four spectra are similar and typical of welldissolved PDI-based chromophores.…”
Section: Uv/vis Absorption and Emissionmentioning
confidence: 99%
“…We believe that the diffuse emission of the dimer is due to either a symmetry-breaking charge-transfer process or a folded geometry, both of which have previously been observed for rigid rylene bisimide systems. [19,39] PDI 4 e has an emission maximum at 596 nm with a high energy shoulder at 560 nm. PDI 4 i has only a broad emission centered at 604 nm.…”
Section: Uv/vis Absorption and Emissionmentioning
confidence: 99%